Emerging materials for transition: A taxonomy proposal from a design perspective - Sofia Soledad Duarte Poblete; Alessia Romani; Valentina Rognoli (Sustainable Futures, 2024)
In response to environmental challenges, design promotes emerging materials connected with the circular economy and environmental sustainability. However, there is confusion about their definition and contribution to sustainable design and production, showing a gap in their classification. This article proposes a taxonomy as a helpful tool to consolidate and unify terminology, definitions and general understanding of these emerging materials. An analysis of 31 real-world case studies helped outline the taxonomic proposal to formalise knowledge, fostering clarity in classifying and identifying them. The taxonomy aims to organise emerging materials, generate reflections, and encourage their responsible development, diffusion, and adoption.